Translational control by 3′-UTR-binding proteins - Szostak, Emilia (Oxford University Press, 2013)
The regulation of mRNA translation is a major checkpoint in the flux of information from the transcriptome to the proteome. Critical for translational control are the trans-acting factors, RNA-binding proteins (RBPs) and small RNAs that bind to the mRNA and modify its translatability. This review summarizes the mechanisms by which RBPs regulate mRNA translation, with special focus on those binding to the 3′-untranslated region. It also discusses how recent high-throughput technologies are revealing exquisite layers of complexity and are helping to untangle translational regulation at a genome-wide scale.